(untitled) - Kazuyoshi, Kamioka (Singapore, 1986)
This book introduce about structure of business and the character of a nation. Eight who built up corporate empires. Problems of the Japanese way of management.
Keywords: Quản trị công nghiệp,Industrial management; Nhật Bản,Japan